Pemulihan dan pengembangan ekonomi kreatif olahan hasil laut di Pesisir Bulak Surabaya pada era new normal untuk menunjang pertumbuhan ekonomi (Recovery and development of creative economy processed sea products in coastal Bulak Surabaya in new normal era for supporting economic growth) - Wurlina, W; Racmawati, Kadek; Utama, Suzanita; Mahasri, Gunanti; Suwasanti, Niluh; Putri, Desak Ketut Sekar Cempaka (Buletin Pengabdian, 2021)
The Regional Prominence Product Development Program (RPPDP) aims to determine the impact of thecoronavirus disease2019(COVID-19)pandemic on Micro, Small, and Medium Enterprises (MSMEs) based on the creative economy of seafood culinary in Bulak, Surabaya. This program was conducted to find out the solution that can be taken by government to recover and develop the creative economy of seafood culinary entrepreneur due to the COVID-19 pandemic impacts. Data were collected by interview/questionnaire, literature review, and implementation of recovery of the the creative economy of seafood culinary. The period of this study was from March (the beginning of the COVID-19 pandemic in Indonesia) to the middle of December 2020. The results of RPPDP showed that there were two elements influenced the seafood culinary entrepreneur due to the COVID-19 pandemic, namely Human Resources and innovation processing and marketing products. The government can take steps to overcome these problems, such as providing business capital assistance, giving discounts on electricity bills, deferring loan payments, assisting MSMEs who closed their businesses as result of the pandemic to transform or start new businesses. In conclusion, innovation of seafood culinary during the pandemic should be in accordance with the market demand, innovating traditional souvenirs to be work from home snacks, and online marketing using non-cash payment.